Determination of refractive index of air along the ray based on the effect of absorption line broadening of air molecules - Remayeva, O.A.; Sokolinskyi, K.A. (Radiotekhnika, 2018)
Due to the large-scale use of GPS technology, the accuracy of determining the location of the object under investigation is of high importance. The effect of absorption of the basic molecules of air on the value of refractive index was examined. Based on these studies a method was developed for determining the magnitude of the average integral refractive index of air, and the errors in the method were investigated. The method for determining the integral average value of air refractive index is developed on the basis of these investigations. The accuracy of the method was studied.